TINJAUAN YURIDIS PENEGAKAN HUKUM UNTUK PERLINDUNGAN KONSUMEN DALAM UPAYA PENINGKATAN MUTU PRODUKSI - Budi Waskito (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2019)
Globalization as a result of the rapid progress in the field of transportation and communication turned out to cause greater dependence between nations, then also the emergence of increasingly sharp levels of competence. Increasing competition brings demands on product quality and higher levels of efficiency. The study discusses how the responsibility of business actors (producers) in consumer protection law is seen from the guarantee of production quality and how law enforcement of consumer protection in improving the quality of national production. The research method used is normative research so that the data used comes from literature, books, and other literature materials. The results of this study are the responsibilities of business actors in consumer protection to guarantee the quality of production are prohibitions to businesses in producing a product, fulfillment of consumer rights, the benefits of standardization of production quality and enforcement efforts in consumer protection not only in resolving consumer disputes to provide the rights and obligations of consumers in consumer dispute cases, but must start from the efforts of supervision and standardization of production quality. Keywords: Law Enforcement, Consumer Protection, Production Quality.